The impact of smartphone addiction and negative emotions on parent–child relationships among elementary school students - Geng, Ze; Liu, Ran (Frontiers in Psychiatry, 2025)
BackgroundThe widespread prevalence of smartphones has profoundly influenced the lives of individuals across all age groups, with children being particularly affected. The issue of smartphone addiction among primary school students has emerged as a global concern as it gives rise to a multitude of adverse outcomes, including depression, anxiety, and strained parent–child relationships.AimsThis study investigated correlations among smartphone addiction (encompassing four dimensions: loss of control, withdrawal, escapism, and inefficiency), negative emotions, and parent-child relationships, while exploring how these factors interact.MethodsData were collected from 1,144 Chinese primary school students (aged 6–15) via parent-completed questionnaires: the Mobile Phone Addiction Index (MPAI), Emotion Questionnaire, and Child-Parent Relationship Scale (CPRS). Structural equation modeling (SEM) analyzed relationships among variables.Results1. Smartphone addiction dimensions divergently impacted emotions: Withdrawal and inefficiency exacerbated negative emotions and emotional regulation difficulties, while loss of control and escapism partially alleviated them—a novel finding challenging traditional unidimensional addiction frameworks. 2. Differential effects of smartphone addiction on parent - child relationships: Loss of control correlated with positive parent-child intimacy; withdrawal increased conflict and dependence; escapism reduced conflict and dependence; inefficiency led to high conflict, high dependence, and low intimacy. 3. The impact of emotions caused by smartphone addiction on parent - child relationships: Negative emotions and emotional regulation difficulties significantly worsened parent-child relationships, manifesting as reduced intimacy, increased conflict, and heightened dependence.ConclusionThis study explored the relationships among smartphone addiction, negative emotions, and parent-child relationships in primary school students. Different dimensions of addiction have different impacts on negative emotions and emotional regulation. Both addiction and negative emotions significantly affect parent - child relationships. The research results are of great significance to researchers, educators, and parents, and can help promote children’s healthy growth and harmonious parent - child relationships.